Effect of country image on trust in social media companies : Case TikTok - Kahelin, Aapo (My University, 2023)
The countries behind various technology companies are currently driving high level decision making and restrictions around the globe. Particularly Chinese tech companies like Huawei and TikTok have faced restrictions and being locked out of foreign markets because of their relationship with the Chinese government. In consumer behaviour countries-of-origin (COO) have been long research as drivers of behaviour. A research gap however exists in COO or country image (CI) research with regard to digital services. In this research the goal was to find out whether the COO of a social media service effects the level of trust consumers place on that service and the extent that they are willing to engage with it. Being able to establish this connection would not only open up a new are of research within CI and trust fields of research but could also have practical implications for the marketing efforts of companies and whole countries. It could also help governments in driving efforts to restrict the use of services of undesirable origin. To figure out whether this possible connection exists quantitative research methods were utilized. A theory of reasoned action (TRA) based framework was created utilizing prior literature on CI and online trust. An online survey was then created based on this framework and answers were gathered from Finnish university students. This data was then analysed using structural equation modeling. Evidence was found in favour of previously established connections between trust, subjective norms and information sharing. However quite little evidence was found for the theorized connection between these and CI. However evidence was found for a partial mediated effect. As a result it can be concluded that CI does play some kind of effect into trust towards social media services and willingness to share information on them. These findings could possibly encourage further research and model development efforts into this are of study.
Keywords: Country image, country-of-origin, trust, privacy, information sharing, social media